Dose Responses of Selected Weedy Rice Accessions, and Commercial Rice Lines and Varieties to Bensulfuron-Methyl - B.B, Baki; M.N, Khan; L, Japareng (Malaysian Journal of Science, 2002)
Dose responses of weed and crop species to herbicides form one of the basis of selectivity, delineating them into tolerant and susceptible types, species or varieties. A laboratory experiment was conducted to assess the differential response of weedy rice accessions, traditional rice varieties, and modem rice lines and varieties to bensulfuron-methyl. Dose response of weedy rice accessions and rice lines and varieties to the herbicide varied considerably with the rice line ACC 8474 being the most tolerant and weedy rice accession PA2 the most susceptible based on the respective seed germination scores of 99.7 and 38.9%. Based on the shoot length and at the dose up to 100 $μ g$ $g^{-1}$, rice lines ACC 4557 and ACC 8460 were most tolerant while the traditional rice variety PT and rice line ACC 4552 were most susceptible to bensulfuron- methyl. The respective $I_{50}$ values of the tolerant rice lines were 51.9 and 28.8$μ g$ $g^{-1}$. The parallel $I_{50}$, scores for the susceptible counterparts were 3.3 and 2.3$μ g$ $g^{-1}$ respectively. Other tolerant rice lines include ACC 8460 and ACC 581 with the $I_{50}$ respective values of 1.8 and 1.3. The $I_{50}$ scores for the susceptible rice line ACC 1041 and weedy rice PAI were $9.2 × l0^{-3}$ and $1.2 × 10^{-2}$ $μ g$ $g^{-1}$, respectively.